Effect of Secondary Phases on 475°C Embrittlement of 1.4462 and 1.4501 Duplex Stainless Steels at Short-term Heat Treatment Conditions - Kısasöz, Alptekin; Özer, Gökhan; Karaaslan, Ahmet (IOP Publishing Ltd, 2019)
Duplex stainless steels (DSSs) are classified according to their chemical composition. Also, the formation of the secondary phases can be defined as a main problem of the DSSs. In this study, decomposition of chromium and iron was studied at short-term heat treatment conditions, and also the effect of the intermetallic phase on the decomposition of chromium and iron was investigated. 1.4462 duplex stainless steel (DSS) and 1.4501 super duplex stainless steel were used in experimental studies. Both alloys were aged at 800 °Cfor 30 min for obtaining the intermetallic based sigma phase. Then, sigma-free and sigma-containing samples for both 1.4462 and 1.4501 alloys were treated at 475 °Cfor 24 h and 75 h, respectively. Samples were characterized by an optical microscope (OM) and scanning electron microscope (SEM). Effect of sigma phase on the formation of 475 °Cembrittlement was conducted by electron diffraction analysis (EDS) and Vickers hardness measurements. It was determined that decomposition of the chromium and iron in a ferrite grain is accelerated by the presence of sigma phase. Sigma phase morphology and the ratio of the alloys did not change for both alloys during the heat treatment processes at 475 °C. Also increasing chromium content promoted the decomposition of chromium and iron in the ferrite phase. It was clearly shown that the sigma is more detrimental to the corrosion properties compared to the decomposition of chromium/iron at 475 °C.
Keywords: Duplex Stainless Steels (DSSs); 1.4462 Alloy; 1.4501 Alloy; Heat Treatment; Corrosion Behaviour